P-87 Are asbestos and strong inorganic acid mists the only occupational exposures that increase laryngeal cancer risk in the construction industry?. (14th March 2023) - Barul, Christine; Gene, Kendya; Luce, Daniele
Abstract : Introduction: Working in the construction industry might entail a complex set of exposures, including a wide range of chemicals such as asbestos and strong acid mists, the only known laryngeal occupational carcinogens. Examining the role of specific tasks performed by construction workers, taking into account their occupational exposure to asbestos and strong inorganic acid mists, could highlight the presence other potential agents that could play a role in laryngeal cancer risk. Objective: We aimed to investigate the association between the detailed circumstances of construction work and laryngeal cancer risk. Material and Methods: Analyses were restricted to men and included 2, 686 population controls and 423 cases of squamous-cell carcinoma of the larynx. Work in the construction industry and potential confounders were assessed by detailed questionnaires. Odds ratios (ORs) and confidence intervals (95%CI) were estimated by unconditional logistic regression, adjusted for age, area of residence, tobacco smoking, alcohol consumption, and occupational exposures to asbestos and strong inorganic acid mists. Results: After adjustment, having ever worked in the construction industry was associated with an increased risk of laryngeal cancer (OR=1.92 95%CI 1.39 to 2.67). Elevated ORs of 1.86 (95%CI 1.25 to 2.76) and 2.56 (95%CI 1.46 to 4.50) were found in men with the shortest and medium total durations of work in the sector, respectively, while no increased risk was found in those who had worked longer. Preliminary results on more detailed aspects showed an increased risk of laryngeal cancer associated with having ever worked in a new construction site (OR=1.81 95%CI 1.23 to 2.67), a renovation project (OR=1.79 95%CI 1.20 to 2.69) or in the civil works sector (OR=1.96 95%CI 1.11 to 3.44). Conclusion: Our findings suggest that besides asbestos and strong inorganic acid mists, other agents found in the construction industry may increase the risk of laryngeal cancer.